The efqm excellence model in the autonomus region of galicia (spain) put to the test - Estrella Vidal Vázquez; Manuel Martínez Carballo (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Business Excellence Models are strategic tools that constitute the most evolved stage in the progress of the quality and proper management the principles which it is based favors the achievement of greater flexibility and swift response in organizations. Based on this assumption, the aim of this study is focused on performing an analysis of the implementation of Total Quality Management through the European Excellence Model on companies of the Autonomous Region of Galicia (Spain). Therefore, first of all, we deal with the management principles on which sits Total Quality Management and discusses its role as a competitive strategy in organizations. Afterwards, we analyze the EFQM Excellence Model as the basis of this research, and finally we summarize the results, which show how leadership and key results are best managed categories, while people results and society results represent areas of improvement in Galician entities that should be improved on their way to excellence.
Keywords: 650; Quality; Total Quality; EFQM; Excellence